MODEL OF SOAP BUBBLES FOR SCIENCE TEACHING - Jahjouh, Yahya Mohmmad Abu (Sanata Dharma University Yogyakarta, 2022)
This paper suggested a model of soap bubbles for science teaching. To be employed in various subjects of science, so to be being used in other study subjects. The model consists of five consecutive stages, engagement, exploration, explanation, elaboration, evaluation. The engagement phase focuses on stimulating students' thinking. In exploration phase, students are concerned with practical activities to solve scientific problems. While the explanation phase, seeks to getting students solve the problems and answers the questions. In elaboration phase, provide opportunities for students to verify their understanding, broaden their perception. In evaluation phase, ensuring that students understand the concepts learned or acquired skills. In addition, the model has basis, clarifies its principles, and has five rules: continuous stimulation of the learners, teaching based on learners' freedom, the integration of traditional methods with modern methods, mutual, equal and equilibrium cooperation of all groups, and a comprehensive, diverse and participation evaluation of all parties in the teaching. The researcher explained the conditions for his success, precautions to be avoided, characteristics, tasks of the learner, and the roles of the teacher, not to mention learning outcomes.